Determinan Kejadian Preeklamsia Di Rumah Sakit Umum Dr. Doris Sylvanus Palangka Raya - Lensi Natalia Tambunan; Angga Arsesiana; Ana Paramita (Jurnal Surya Medika (JSM), 2020)
Preeclampsia is the problem and can threaten soul mothers during pregnancy, giving birth, and the fetus. Mother maternity with preeclampsia in BLUD dr. Doris Sylvanus Palangkaraya's rise in 2015 amounted to 14,2% of 2014 namely 12,3% and there is one of the deaths of the mother caused by preeclampsia. Factors affecting the occurrence of preeclampsia are Antenatal Care (ANC), a history of hypertension, age, parity, double pregnancy, use of birth control contraceptives, employment, education, health insurance. The purpose of the research is to know the dominant factors affecting the occurrence of preeclampsia in the BLUD Dr. Doris Sylvanus Palangka Raya Central Kalimantan province year 2017. The design of this research is the quantitative observation of observational analytic using the type of case-control study design. The case is the entire maternity mother with preeclampsia as much as 81 people and the control is no preeclampsia maternity mother as much as 162. Samples taken randomly are simple. Data analyzed in a descriptive and Chi-square. The results of the analysis showed that 55.6% of maternity mothers with preeclampsia seldom/never conducted an ANC examination. There are 2 significant variables associated with preeclampsia in maternity mothers, Antenatal Care (ANC), and the history of hypertension. It can be concluded, the Antenatal Care (ANC) factor and the history of hypertension relate to preeclampsia in maternity mothers. It is recommended for midwives to conduct supervision in expectant mothers who conduct an ANC examination with a history of hypertension and collaborate with specialist doctors.